The effect of hypoxia exercises on some blood gases and cells of adolescent swimmers - Rahimi, A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of the research was to study the effect of hypoxia exercise on some blood biochemical parameters of adolescent swimmers. The findings suggest that performance of this kind of exercise program may shift oxyhemoglobin dissociation curve to the right with increasing Pco2 and decreasing pH (Borh effect). In conclusion decreasing the affinity of oxygen to hemoglobin and oxygen is released faster than Hb and transmissibility, absorption and consumption of oxygen in active tissues also in skeletal muscles in increase.